2008
DOI: 10.1016/j.cub.2007.12.055
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian SPD-2 Ortholog Cep192 Regulates Centrosome Biogenesis

Abstract: Centrosomes are the major microtubule-organizing centers of mammalian cells. They are composed of a centriole pair and surrounding microtubule-nucleating material termed pericentriolar material (PCM). Bipolar mitotic spindle assembly relies on two intertwined processes: centriole duplication and centrosome maturation. In the first process, the single interphase centrosome duplicates in a tightly regulated manner so that two centrosomes are present in mitosis. In the second process, the two centrosomes increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
218
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(236 citation statements)
references
References 38 publications
(76 reference statements)
11
218
1
Order By: Relevance
“…Indeed, we found Cep192/oligomerization-mediated AurA activation to be critical for the function of MTOCs, both natural (centrosomes) and artificial (αAurA-coated beads). Parenthetically, the AurA-Cep192 function, reported here, is independent of centriole duplication/assembly (3,5,6), because exogenous, sperm nuclei-derived centrioles did not duplicate under the experimental conditions used (metaphase-arrested extract) (1, 2) and remained intact through the experiment (Fig. 3 A and D).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Indeed, we found Cep192/oligomerization-mediated AurA activation to be critical for the function of MTOCs, both natural (centrosomes) and artificial (αAurA-coated beads). Parenthetically, the AurA-Cep192 function, reported here, is independent of centriole duplication/assembly (3,5,6), because exogenous, sperm nuclei-derived centrioles did not duplicate under the experimental conditions used (metaphase-arrested extract) (1, 2) and remained intact through the experiment (Fig. 3 A and D).…”
Section: Discussionmentioning
confidence: 66%
“…These observations suggest that the function of αAurA beads as MTOCs is a product of αAurA/dimerization-mediated AurA activation occurring on the bead surface. (3)(4)(5)(6), suggested that a common, Cep192-driven process underlies the development of MTOC activity by both centrosomes and αAurA beads. To explore this notion, we isolated a Xenopus laevis Cep192 cDNA encoding a 2,638 amino acid (aa), 289-kDa protein and raised Cep192-specific N-and C-terminally directed antibodies (αCep192-N and αCep192-C, respectively) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPD-2/ Cep192 proteins are recruited in the immediate vicinity of the centrioles and play a key role in organizing the PCM by recruiting CNN/CDK5RAP2 and microtubule-nucleating complexes [3,4,119]. Caenorhabidtis elegans and human SPD-2 homologues are also required for centriole duplication, but possibly indirectly through their ability to recruit PCM, as Drosophila SPD-2 is dispensable for centriole duplication [119][120][121]. Remarkably, an SPD-2 orthologue is encoded in the Dictyostelium genome and localizes to the corona that surrounds the NAB, which is functionally equivalent to the PCM [40].…”
Section: Is the Molecular Composition Of The Centrosome Conserved?mentioning
confidence: 99%
“…Another possibility is that SPD-2 originally evolved to organize the poles of the mitotic spindle in Amorphea. In animals, SPD-2 family members are key to centrosome maturation, which leads to an increase in the microtubule-nucleation capacity of mitotic centrosomes required for centrosome-driven spindle assembly [121,123,124]. In chytrids and choanoflagellates, mitotic microtubules are nucleated in the immediate vicinity of the centrioles, which could involve SPD-2-dependent recruitment of microtubule-nucleating complexes.…”
Section: Is the Molecular Composition Of The Centrosome Conserved?mentioning
confidence: 99%